PENGARUH PERSEPSI SISWA TENTANG AKHLAK GURU TERHADAP KEDISIPLINAN SISWA (KELAS IV,V,VI) PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SD NEGERI 003 PULAU JAMBU CERENTI - Shindi Napalia; Sopiatun Nahwiyah; Ikrima Mailani (AL-HIKMAH (Jurnal Pendidikan dan Pendidikan Agama Islam), 2020)
The problem in this research is students come late to school because the teacher does not arrive on time, students are lazy to do homework given by the teacher. At the time the bell was ringed there were still students who ate in the cafeteria, because the teacher was late in class. Students came out of the yard during school hours without the teacher's knowledge. In general, this study aims to determine the effect of student perceptions of teacher morals on student discipline (class, IV, V, VI) on Islamic Religious Education subjects at SD Negeri 003 Jambu Cerenti Island. The research method used was a quantitative study, the population of this study was 92 students, while the sample the author took as many as 50 students. Data collection techniques using, observation, interviews, documentation and questionnaires. Data Analysis Techniques used are simple linear regression techniques. After calculating, the authors draw the conclusion that, "there is an effect of students' perceptions of teacher morals on student discipline (class, IV, V, VI) on Islamic religious education subjects at SD Negeri 003 Jambu Cerenti Island." Based on the hypothesis test, at a significant level of 5% is obtained Fhit = 2,591 and Ft = 1,677, so Fhit> Ft means that Ho is rejected and Ha is accepted.